The Effects of Water Deficiency on Plant and Tuber Growth of Kohlrabi (Brassica oleracea L. var gongylodes) - Kamile Ulukapı; Yusuf Kacar (Turkish Journal of Agriculture: Food Science and Technology)
Kohlrabi, which has increased production in our country in recent years, is a vegetable with high water consumption. The aim of this study was to determine the effects of different irrigation levels on plant and tuber growth and determine the appropriate irrigation level. In this study, vegetative growth and some tuber quality parameters of two different kohlrabi cultivars (Korist F1, Kolibri F1) at 4 different irrigation levels (I100 I75, I50, I25) were investigated. The experiment was carried out in unheated greenhouse as a pot experiment in April-June with three replicates and 10 plants per replicate. At the end of the experiment; number of leaves, leaf width (mm), leaf length (mm), tuber diameter (cm), tuber height (cm), tuber weight (g), tuber pH, total soluble solid content of the tuber and chlorophyll index were measured. The growth curves of the tubers were drawn and potassium (K), phosphorus (P) and sodium (Na) contents of the tubers were determined. In Kolibri F1, the highest tuber weight was obtained from the I75 irrigated plants with an average of 369.59 g. In Korist F1, the highest tuber weight was obtained from I100 applied plants with an average of 362.25 g. Especially in terms of tuber development, I100 has provided better results in water deficiency application. However, according to the results of the analysis, there was no statistically significant difference between I100 and I75 irrigation levels. It was determined that I75 irrigation level could be applied for kohlrabi cultivars in April-June cultivation period in Antalya conditions.